THE ROLE OF SYMBIOTIC ZOOXANTHELLAE ON GIANT CLAM NUTRITION - Ambariyanto . (JOURNAL OF COASTAL DEVELOPMENT, 1997)
Zooxanthellae, Symbiodinium sp, are single cell dinoflagellate algae known to live in association with many marine invertebrates such as hermatypic corals, sea anemones, jellyfish and giant clams (family Tridacnidae). In giant clams, these photosynthetic algae are located in a tubular system (known as Z tube system) which occurs within the clams. Apart from filter feeding, the nutrition of the clams is provided by zooxanthellae. These algae are capable of translocating part of their photosynthetic products to the host. CZAR values are also discussed.